STUDENTS’ UNDERSTANDING OF NOMINAL SENTENCE AND VERBAL SENTENCE - Yani Lubis; Nazila Fujianti Rambe; Ananda Tahara; Rahmadania Purba; Riana (Cemara Education and Science, 2025)
This study aims to investigate students’ understanding of nominal and verbal sentences. A good understanding of this sentence types is important for strong english language skill, especially in writing and speaking. This study uses a qualitative approach to analyze students’ ability to distinguish and use nominal and verbal sentences. The research findings are expected to provide an overview of the students’ level of understanding. The results show that students still have difficulties in distinguishing between the two types of sentences. The most common error is the writing of the sentence. This study also aims to identify areas that require improvement in the teaching of grammar. With a better understanding of nominal and verbal sentences, students can improve their proficiency in english.